1999
DOI: 10.1007/s002449900493
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 4-Chloroaniline in Early Life Stages of Zebrafish ( Danio rerio ): II. Cytopathology and Regeneration of Liver and Gills After Prolonged Exposure to Waterborne 4-Chloroaniline

Abstract: Ultrastructural alterations in liver and gills of embryonic and larval zebrafish (Danio rerio) following prolonged exposure to waterborne 0.05, 0.5, and 5 mg/L 4-chloroaniline for up to 31 days as well as after a 14-day regeneration period were investigated by means of light and electron microscopy. Acute toxicity was also tested at 25 and 50 mg/L. Survival of zebrafish embryos and larvae was only impaired from 25 mg/L 4-chloroaniline, but-after a transient stimulation following exposure to 0.5 mg/L-4-chloroan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 0 publications
3
36
0
2
Order By: Relevance
“…This layer may affect close adaptation between root canal filling materials and the root canal walls, interfering in the seal of the root canal filling (8,9). In addition, this precipitate changes the color of the tooth and is cytotoxic (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This layer may affect close adaptation between root canal filling materials and the root canal walls, interfering in the seal of the root canal filling (8,9). In addition, this precipitate changes the color of the tooth and is cytotoxic (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…These findings might be clinically relevant because PCA has been shown to be toxic (30,31). Toxicologic studies in animals have shown that the hematopoietic system is the major target for PCA (30).…”
Section: Discussionmentioning
confidence: 92%
“…The primary toxic effect of PCA is the formation of methemogloblin. Studies have shown that methemoglobin formation and hemolytic anemia occurred in animals after 90-day exposure to PCA (31). A carcinogenic effect of PCA in rats, manifested by increased sarcomas in the spleen, was also reported.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A carcinogenic effect by an increase in sarcoma formation in the spleen has also been reported (8). Another reported adverse effect of PCA was a delay in egg hatching and an increased rate of abnormal development and pigmentation in the hatchlings of zebra fish (18). Adverse effects have also been shown to occur in the embryos of Daphnia magna (19).…”
Section: Relevance Of Para-chloroanilinementioning
confidence: 95%